Schiff Base Crosslinked Hyaluronic Acid Hydrogels with Tunable and Cell Instructive Time-Dependent Mechanical Properties - Behroozi Kohlan, Taha; Finne-Wistrand, Anna (Royal Institute of Technology, 2024)
This folder contains raw data for the paper titled "Schiff Base Crosslinked Hyaluronic Acid Hydrogels with Tunable and Cell Instructive Time-Dependent Mechanical Properties" authored by Taha Behroozi Kohlan, Yanru Wen, Carina Milena Mini, and Anna Finne-Wistrand, published in Carbohydrate Polymers journal. The raw data presented here contains NMR, FTIR, SEC, swelling and stability, and rheology data used to create figures.

Abstract:

The dynamic interplay between cells and their native extracellular matrix (ECM) influences cellular behavior, imposing a challenge in biomaterial design. Dynamic covalent hydrogels are viscoelastic and show self-healing ability, making them a potential scaffold for recapitulating native ECM properties. We aimed to implement kinetically and thermodynamically distinct crosslinkers to prepare self-healing dynamic hydrogels to explore the arising properties and their effects on cellular behavior. To do so, aldehyde-substituted hyaluronic acid (HA) was synthesized to generate imine, hydrazone, and oxime crosslinked dynamic covalent hydrogels. Differences in equilibrium constants of these bonds yielded distinct properties including stiffness, stress relaxation, and self-healing ability. The effects of degree of substitution (DS), polymer concentration, crosslinker to aldehyde ratio, and crosslinker functionality on hydrogel properties were evaluated. The self-healing ability of hydrogels was investigated on samples of the same and different crosslinkers and DS to obtain hydrogels with gradient properties. Subsequently, human dermal fibroblasts were cultured in 2D and 3D to assess the cellular response considering the dynamic properties of the hydrogels. Moreover, assessing cell spreading and morphology on hydrogels having similar modulus but different stress relaxation rates showed the effects of matrix viscoelasticity with higher cell spreading in slower relaxing hydrogels.
Keywords: Chemical Sciences; Kemi